Phenomenological exploration of the strengths and weaknesses of work and technology curriculum implementation and strategies to improve its implementation - zahra abolhasani; marziyeh dehghani; mohamad javadipour; Keyvan Salehi; nasrin mohamad hasani (Shahid Chamran University of Ahvaz, 2021)
IntroductionDue to the usability of the work and technology curriculum in life, as well as its important role in motivating and aspiring to jobs in society and helping to choose a field, the country's educational system has paid special attention to the work and technology curriculum. The purpose of this study was to qualitatively review the challenges and strengths of the work and technology curriculum and strategies to improve the implementation of the work and technology curriculum. MethodFor this purpose, the phenomenographic method was used. Targeted sampling method with snowball technique was available for experts and targeted teachers, number of participants according to data saturation 6 experts; 25 teachers were selected. Semi-structured interviews were used to collect data. Data analysis was performed using a 7-step clays method. To validate the data strategies such as data collection triangulation; Interviewees' reviews of the impressions and codings and the review of the collaborating researchers and the agreement between the researcher and the participants in the research were used.ResultsResearch results in three sections: challenges and obstacles to implementation; The strengths of the work and technology curriculum and the proposed solutions to improve this were obtained from the perspective of experts and teachers.DiscussionFindings were obtained from the perspective of teachers and experts that the challenges and obstacles to the implementation of work and technology course include five themes "limitation, teacher, content relevance, comprehensive evaluation system, social factors" with eleven sub-themes "facilities, financial resources, physical space , Time, specialized teacher, skill category (knowledge enhancement), disproportion to the need, imbalance in content, weakness in the implementation of evaluation, lack of cultural background, low status and value of work and technology among officials "and the strengths of the two "Technical aspect, knowledge-building" and five sub-themes "entrepreneurship, appropriate academic guidance, creativity, craftsmanship, general skills" and in the solutions two themes "improving curriculum elements, motivating" and six sub-themes "content, evaluation" "Facilities, hidden curriculum, communication channels, salaries and benefits."